Optimalisasi Peran Guru Dan Orang Tua Dalam Meningkatkan Karakter Religius Peserta Didik Madrasah Ibtidaiyah - Wulandari, Rizki Isma; Ichsan, Ichsan (Alifbata : Jurnal Pendidikan Dasar, 2023)
This research is motivated by the attention of researchers to the role of teachers and parents in developing the religious character of students. The purpose of this research is to analyze how to optimize the role of teachers and parents in improving the religious character of students. This research was conducted at MIN 1 Mataram City, NTB in the 2021/2022 academic year. Participants consisted of class teachers, principals, two students, and three parents. This research uses a qualitative approach with a descriptive type. The method of data collection is carried out through interviews, observation, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion. The results of this study indicate that efforts to optimize the role of teachers and parents in improving the religious character of students in learning are by carrying out habituation programs such as the morning Qur'an, praying, praying dhuha in the congregation, shaking hands with the teacher, and exemplary from teachers and parents by establishing cooperation between the two through the media of student worship control books which are then signed by teachers and parents, parental involvement in children's learning at home, and collaboration with community groups. Therefore, to improve the religious character of students, the role of teachers and parents is very important by guiding, familiarizing, and setting an example optimally.